Diseño de un portaempaque para el revestimiento de un pozo de extracción de petróleos (2019)
In this project a design of a packer in the oil industry was made.It starts with what type of packeris going to be designed to later perform all the detailed design calculating forces, effort, and dimensions of the tool. The simulation is carried out to corroborate the results obtained. Finally, the assembly, operation and maintenance manuals are carried out. The financial evaluation is performed to obtain the total cost of the tool. Additionally, the manufacturing drawings of each of the pieces of the packer are made.